International Turkish sea power history symposium, 20-22 October 2008, İstanbul : the Indian Ocean and the presence of the Ottoman navy in the 16th and 17th centuries. (İstanbul)
xvi, 44, 55, 54, 72, 37, 35, 15, 11, 40, 11, 26 s.